Minimum wages in Poland as a contradiction of European Union’s basic objectives - Księżyk, Marianna; Duda, Jerzy (Managerial Economics, 2012)
Poland being an EU country should achieve the basic objectives of the Community, such as: prosperity, peace, democracy and human rights, which should mean in practice transferring economic growth into increase of living standards of the country population and creating of 159 Summaries an egalitarian society. Guided by this assumption the subject of the paper is to analyze the minimum wages in Poland in comparison with the EU countries. By this analysis it was found that the level of minimum wages in Poland stays throughout the whole period of the economy transformation, particularly in relation to the EU-15, at a very low level and does not meet the requirement of fair wages. Besides the fact that such a low level of minimum wages in Poland cannot be justified by labor costs, neither labor time nor labor productivity.